Mathematical modelling of a crop irrigation problem - Nazir Kamal Rahim (2019)
Agriculture is extremely important in providing food globally. To meet the needs of crop growth, unnatural application of water, otherwise known as irrigation, has been implemented as a solution to counter inconsistent rainfall. Out of the various methods of irrigation employed, furrow irrigation will be looked into and analyzed in this project. This paper will deal with the design of furrow irrigation channels, particularly in the spacing of these channels. The aim is to achieve an optimal spacing through a mathematical model in the form of an analysis which involves the formulation of boundary value problems as well as the numerical solutions. The numerical solutions will be programmed to obtain the suction potential which is the primary variable of comparison for this project. This paper will subsequently go on to investigate the relationship between certain variables mwith the suction potential. The study of these relationships will provide a possible practical implementation that can be of benefit to others.